Microbial quality and phylogenetic diversity of fresh rainwater and tropical freshwater reservoir. - Rajni Kaushik; Rajasekhar Balasubramanian; Hugh Dunstan (PLoS ONE, 2014)
The impact of rainwater on the microbial quality of a tropical freshwater reservoir through atmospheric wet deposition of microorganisms was studied for the first time. Reservoir water samples were collected at four different sampling points and rainwater samples were collected in the immediate vicinity of the reservoir sites for a period of four months (January to April, 2012) during the Northeast monsoon period. Microbial quality of all fresh rainwater and reservoir water samples was assessed based on the counts for the microbial indicators: Escherichia coli (E. coli), total coliforms, and Enterococci along with total heterotrophic plate counts (HPC). The taxonomic richness and phylogenetic relationship of the freshwater reservoir with those of the fresh rainwater were also assessed using 16 S rRNA gene clone library construction. The levels of E. coli were found to be in the range of 0 CFU/100 mL-75 CFU/100 mL for the rainwater, and were 10-94 CFU/100 mL for the reservoir water. The sampling sites that were influenced by highway traffic emissions showed the maximum counts for all the bacterial indicators assessed. There was no significant increase in the bacterial abundances observed in the reservoir water immediately following rainfall. However, the composite fresh rainwater and reservoir water samples exhibited broad phylogenetic diversity, including sequences representing Betaproteobacteria, Alphaproteobacteria, Gammaproteobacteria, Actinobacteria, Lentisphaerae and Bacteriodetes. Members of the Betaproteobacteria group were the most dominant in both fresh rainwater and reservoir water, followed by Alphaproteobacteria, Sphingobacteria, Actinobacteria and Gammaproteobacteria.